2020
DOI: 10.21203/rs.3.rs-24733/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilient care of the patient with COVID-19 in Iran: A phenomenological Study

Abstract: Background Family caregivers understand several challenges in caring for patients with COVID-19.This study aimed to understand the experiences of Iranian family caregivers of persons with COVID-19. Method: This study utilized phenomenological hermeneutic design. Fourteen Iranian family caregivers of patients with COVID-19 who were quarantined at home were included in the study using purposive sampling. In-depth semi-structured interviews were conducted via WhatsApp. Sampling continued until data saturation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this regard, it is stated that quarantine and restricted interpersonal relationships may result in senses of shame and loneliness which can be tackled by taking these measures for the purpose of recovery and family reunion. In addition, psychiatric nurses are recommended to develop programs in the form of psychological support or comprehensive spiritual care packages and utilize multiple media channels to help patients overcome such feelings [19].The third theme was found to be changes in lifestyle of patients and people. This finding is also emphasized by other studies which showed that the COVID-19 pandemic has disrupted trades and movements all over the world and negatively impacts day-to-day businesses and life.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it is stated that quarantine and restricted interpersonal relationships may result in senses of shame and loneliness which can be tackled by taking these measures for the purpose of recovery and family reunion. In addition, psychiatric nurses are recommended to develop programs in the form of psychological support or comprehensive spiritual care packages and utilize multiple media channels to help patients overcome such feelings [19].The third theme was found to be changes in lifestyle of patients and people. This finding is also emphasized by other studies which showed that the COVID-19 pandemic has disrupted trades and movements all over the world and negatively impacts day-to-day businesses and life.…”
Section: Resultsmentioning
confidence: 99%